2009
DOI: 10.4238/vol8-4gmr668
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous presence of bovine papillomavirus in blood and in short-term lymphocyte cultures from dairy cattle in Pernambuco, Brazil

Abstract: ABSTRACT. Bovine papillomaviruses (BPV) are the causal agents of benign and malignant lesions; they can cause dramatic economic losses in cattle. Although 10 virus types have been described, three types are most common in tumors, namely BPV-1, -2 and -4. Previous studies have reported BPV in blood cells and the possibility of blood acting as a latent virus site and/or transmission agent of virus dissemination. We studied a Holstein dairy herd in Pernambuco, Brazil, in which several animals showed severe cutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
(22 reference statements)
4
22
0
6
Order By: Relevance
“…This study presents important evidence, in association with previous data (Diniz et al, 2009), suggesting that PBMCs act not only as a viral reservoir but also as a disseminator of BPV to other tissues. Thus, this study demonstrated the productive infection in PBMCs, which was verified by the BPV L1 immunodetection and virus-like particles presence in infected cell which high levels of clastogenesis.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study presents important evidence, in association with previous data (Diniz et al, 2009), suggesting that PBMCs act not only as a viral reservoir but also as a disseminator of BPV to other tissues. Thus, this study demonstrated the productive infection in PBMCs, which was verified by the BPV L1 immunodetection and virus-like particles presence in infected cell which high levels of clastogenesis.…”
Section: Introductionsupporting
confidence: 75%
“…The presence of BPV sequences in peripheral blood has already been described in the literature (Stocco dos Santos et al, 1998;Roperto et al, 2008;Diniz et al, 2009;Melo et al, 2011;Araldi et al, 2013b). The peripheral blood does not represent the first site of virus contact, according to the infection pathway commonly described (Florin et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…After conducting the PCR procedure on full blood and lymphocyte cultures belonging to 54 six-year-old Holstein cows, Diniz et al 22 positively identified BPV-1 in 74% (40/54) and BPV-2 nucleic acid in 87% (47/54) of the samples. Yanguiu et al 23 and Freitas et al 24 confirmed the existence of BPV-1 and BPV-2 nucleic acid with the PCR procedure in papilloma samples they collected from cattle clinically diagnosed with cutaneous papilloma.…”
Section: Discussionmentioning
confidence: 99%
“…Así, aunque los PV son considerados virus epiteliotrópicos, se ha detectado la presencia de BPV en diversos fluidos del ganado vacuno como sangre, leche, orina o semen (Yaguiu et al, 2006(Yaguiu et al, y 2008Diniz et al, 2009;Lindsey et al, 2009). Esta situación provoca que las poblaciones estabuladas sean más vulnerables a la diseminación del virus (Nasir y Campo, 2008;Reza, 2008).…”
Section: A B C 46unclassified